Regeneration method of silicon-arsenic poisoning denitration catalyst
Through chemical cleaning methods such as soot blowing, alkali washing, pickling washing and drug washing, combined with drying and calcining steps, silicon and arsenic in the denitrification catalyst of silicon arsenic poisoning were removed, which solved the problem of decreasing catalyst activity and waste of resources, and realized the catalyst's Efficient recycling and sustainable use of resources.
Patent Information
- Application Number
- CN202411645550.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
The denitrition of the activity of denitrification catalysts and waste of resources caused by silicon arsenic poisoning, especially in coal-fired thermal power plants, the catalyst is inactivated due to ash accumulation, wear, sintering and poisoning, and waste catalysts containing heavy metals cause secondary pollution to the environment.
Chemical cleaning methods such as soot blowing, alkali washing, pickling washing and drug washing are adopted, combined with drying and calcining steps, silicon and arsenic on the surface of the catalyst are removed, active substances are supplemented, and the denitrification activity of the catalyst is restored.
Effectively remove silicon and arsenic from the catalyst, improve denitrification efficiency and activity, extend the service life of the catalyst, avoid environmental pollution, and reduce the cost of catalyst replacement.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of denitration catalyst regeneration, and in particular relates to a regeneration method for a silicon-arsenic poisoned denitration catalyst. Background Art
[0002] V2O5-WO3 / TiO2 catalysts are gradually being promoted and widely used in coal-fired power plants. During the flue gas denitrification process, high concentrations of dust and high-temperature airflow in the flue gas will cause the catalyst to accumulate dust, wear, sinter, poison, and become inactive. The service life is generally about 3 years. At the same time, heavy metals such as Si, Fe, and As in the flue gas will be enriched on the catalyst along with the airflow, making it a harmful material containing heavy metals.
[0003] The SiO2 content in high-concentration dust in flue gas can reach more than 44%, and some VO x Species and surface SiO x The species interact and disperse, and this Si-OV bonding makes the dispersed VO x At the same time, the doping of SiO2 also makes V 5+ The reduction of Si content is not conducive to the improvement of the denitrification activity of the catalyst. Therefore, after the Si component is incorporated into the V2O5-WO3 / TiO2 catalyst structure by coprecipitation, the denitrification activity will decrease.
[0004] Arsenic is one of the harmful trace elements in coal, and is mainly combined with pyrite in coal. During the combustion of coal, arsenic species will be released from coal in various forms. For the arsenic-coal system under an oxidizing atmosphere, when the temperature is lower than 427°C, the arsenic in the flue gas exists in the form of As2O5(g); when the temperature is between 427-527°C, As4O6(g), As2O5(g) and AsO(g) coexist, among which As4O6(g) is the main form; and when the temperature is higher than 527°C, arsenic mainly exists in the form of AsO(g).
[0005] Research results show that As4O6 is the main arsenic species in the SCR reactor. There are many pores on the surface of the V2O5-WO3 / TiO2 catalyst. When arsenic-containing flue gas passes through the catalyst, gaseous As2O3 (As4O6) will be deposited on the catalyst surface and in the pores. As time goes by, the deposited arsenic content increases, forming a covering layer on the catalyst surface or blocking the catalyst pores. A small amount of liquid arsenic soluble in water is evenly dispersed on the catalyst surface and in the pores, and is easier to enter the micropores of the catalyst. Therefore, the pore size of the As-poisoned catalyst sample increases, and the micropore volume decreases significantly, which significantly reduces the denitrification activity of the denitrification catalyst.
[0006] If a large number of arsenic catalysts scrapped from coal-fired power plants are directly landfilled, it will not only cause secondary pollution to the water and soil environment, but also cause a huge waste of vanadium, tungsten and titanium resources. If the silicon-arsenic poisoned catalyst is regenerated, it can not only avoid the secondary pollution of the waste catalyst to the environment, but also reduce the cost of catalyst replacement, and reduce the catalyst investment cost for coal-fired power plants. Therefore, a method for regenerating silicon-arsenic poisoned denitrification catalysts is developed to achieve the purpose of resource utilization of waste catalysts. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for regenerating a silicon-arsenic poisoned denitration catalyst, remove silicon and arsenic, and improve the denitration efficiency and activity of the regenerated denitration catalyst.
[0008] The embodiment of the present invention provides a method for regenerating a silicon-arsenic poisoned denitration catalyst, comprising the following steps: 1) Blow off the soot and clean the silicon-arsenic poisoned denitrification catalyst; 2) The cleaned silicon-arsenic poisoned denitrification catalyst is subjected to alkali washing, acid washing and chemical washing; The pickling solution is a mixture of acid and copper corrosion inhibitor; the chemical washing solution is a mixture of hydrofluoric acid and corrosion inhibitor; 3) Then clean it; 4) Supplement active substances; 5) Drying and calcining to obtain the regenerated denitration catalyst.
[0009] Preferably, the soot blowing in step 1) is performed by disassembling the silicon-arsenic poisoning denitration catalyst module, and then reassembling it into a module after soot blowing, and it is required that no soot accumulation is visible in the module.
[0010] Preferably, the cleaning in step 1) is performed by bubbling in an aqueous solution with a pH of 7 to 9, the cleaning liquid-to-solid ratio (solution volume / module mass) is 3 to 5 mL:1 g, the cleaning time is 30 min, and the cleaning temperature is room temperature.
[0011] Preferably, the alkali washing solution in step 2) is a sodium hydroxide or potassium hydroxide aqueous solution with a mass concentration of 5-20%, and the alkali washing temperature is 80-100° C. The cleaning liquid-to-solid ratio (solution volume / module mass) is 3-6 mL:1 g; and the cleaning time is 30 min-120 min.
[0012] Preferably, in the pickling solution in step 2), the acid is sulfuric acid, nitric acid or hydrochloric acid, the copper corrosion inhibitor is BTA (benzotriazole) or TTA (methylbenzotriazole), the pH is controlled to be 3-5, the mass concentration of the copper corrosion inhibitor is 0.1-0.3%, and the pickling temperature is 40-60°C. The cleaning liquid-to-solid ratio (solution volume / module mass) is 3-6mL:1g; the cleaning time is 180min-240min.
[0013] Preferably, in the solution of the drug wash in step 2), the mass concentration of hydrofluoric acid is 3% to 10%, and the mass concentration of the corrosion inhibitor is 0.2% to 0.5%. The cleaning liquid-solid ratio (solution volume / module mass) is 3 to 6 mL: 1 g; the cleaning time is 30 min to 120 min; the cleaning temperature is room temperature, and the corrosion inhibitor is preferably a copper corrosion inhibitor, more preferably BTA.
[0014] Preferably, the cleaning in step 3) is performed by bubbling in an aqueous solution with a pH of 5 to 7, the cleaning liquid-to-solid ratio (solution volume / module mass) is 3 to 5 mL: 1 g, the cleaning time is 120 to 180 min, and the cleaning temperature is room temperature.
[0015] Preferably, the active substances in step 4) are vanadyl sulfate, ammonium metatungstate and ammonium molybdate.
[0016] Preferably, in the active material, the mass concentration of vanadyl sulfate is 0.1% to 6%, the mass concentration of ammonium metatungstate is 0.5% to 4%, and the mass concentration of ammonium molybdate is 2% to 10%.
[0017] Preferably, the drying temperature in step 5) is 150° C. to 200° C., and the drying time is 6 to 12 hours.
[0018] Preferably, the calcination temperature in step 5) is 350° C. to 400° C., and the calcination time is 3 to 6 hours.
[0019] The beneficial effect of the present invention is that the present invention removes silicon and arsenic at the same time to achieve the regeneration of the denitration catalyst. The present invention removes silicon and arsenic on the surface of the denitration catalyst to the greatest extent under acid-base chemical treatment conditions without affecting the mechanical strength of the catalyst. The present invention removes active components in part of the original catalyst, and further improves the denitration performance of the catalyst through the subsequent supplementation of active substances. DETAILED DESCRIPTION
[0020] The preferred embodiments of the present invention will be described in detail below.
[0021] Example 1 A method for regenerating a silicon-arsenic poisoned denitration catalyst comprises the following steps: 1) Dust removal and reassembly: Disassemble the module, blow off the dust from each unit, and then reassemble the units into modules.
[0022] 2) Chemical cleaning: Water cleaning: Use a pH=8 aqueous solution (add sodium hydroxide to water to control the pH to 8) for bubbling cleaning for 30 minutes, the cleaning liquid-solid ratio (solution volume / module mass) is 4mL:1g, and the cleaning temperature is room temperature; Alkaline cleaning: Then, wash in a 5% NaOH aqueous solution by bubbling for 30 min (the temperature is controlled at 80°C), and the cleaning liquid-to-solid ratio (solution volume / module mass) is 4 mL:1 g; Pickling: Immerse the module in a solution containing sulfuric acid and 0.1% BTA (pH controlled at 4), and bubble clean for 180 minutes at 40°C. The cleaning liquid-solid ratio (solution volume / module mass) is 4mL:1g. Chemical washing: the module is then immersed in a solution containing 3% hydrofluoric acid by mass and 0.2% corrosion inhibitor by mass for bubbling cleaning for 30 minutes (temperature is room temperature). The corrosion inhibitor is BTA, and the cleaning liquid-solid ratio (solution volume / module mass) is 4mL:1g.
[0023] 3) Finally, immerse the module in a pH=6 aqueous solution (add hydrochloric acid to water to control the pH to 6) for bubbling cleaning for 120 minutes. The cleaning liquid-to-solid ratio (solution volume / module mass) is 4mL:1g, and the cleaning temperature is room temperature.
[0024] 4) Active material supplementation: The chemically cleaned module is immersed in an active material solution for 15 minutes. The active material solution contains vanadyl sulfate, ammonium metatungstate and ammonium molybdate, wherein the mass percentage of vanadyl sulfate is 0.1wt%, the mass percentage of ammonium metatungstate is 0.5wt%, and the mass percentage of ammonium molybdate is 2wt%.
[0025] 5) Activation: The module obtained in step 4) is dried and calcined to achieve high-temperature activation, with a drying temperature of 150° C. and a drying time of 12 h; and a calcination temperature of 350° C. and a calcination time of 6 h.
[0026] Testing of the regenerated denitrification catalyst revealed that its silicon removal rate reached 84%, arsenic removal rate was 90%, denitrification efficiency was 57.10%, and activity recovered to 96.8%.
[0027] Example 2 A method for regenerating a silicon-arsenic poisoned denitration catalyst comprises the following steps: 1) Dust removal and reassembly: Disassemble the module, blow off the dust from each unit, and then reassemble the units into modules.
[0028] 2) Chemical cleaning: Water cleaning: Use a pH=8 aqueous solution (add sodium hydroxide to water to control the pH to 8) for bubbling cleaning for 30 minutes, the cleaning liquid-solid ratio (solution volume / module mass) is 4mL:1g, and the cleaning temperature is room temperature; Alkaline washing: Then, the module was cleaned by bubbling in a 10% KOH aqueous solution for 120 min (the temperature was controlled at 100°C), and the cleaning liquid-to-solid ratio (solution volume / module mass) was 4 mL:1 g.
[0029] Pickling: The module was immersed in a solution containing nitric acid, hydrochloric acid, 0.1% BTA and 0.2% TTA (pH was controlled at 4), and bubbled for 240 min at 60°C. The cleaning liquid-to-solid ratio (solution volume / module mass) was 4 mL:1 g. The total mass concentration of nitric acid and hydrochloric acid was 0.1%, and the weight ratio of nitric acid to hydrochloric acid was 2:1.
[0030] Chemical washing: The module is then immersed in a solution containing 10% hydrofluoric acid by mass and 0.5% corrosion inhibitor by mass for bubbling cleaning for 120 minutes (temperature is room temperature). The corrosion inhibitor is BTA, and the cleaning liquid-solid ratio (solution volume / module mass) is 4mL:1g.
[0031] 3) Finally, immerse the module in a pH = 6 aqueous solution for bubbling cleaning for 180 minutes. The cleaning liquid-to-solid ratio (solution volume / module mass) is 4mL:1g, and the cleaning temperature is room temperature.
[0032] 4) Active material supplementation: The chemically cleaned module is immersed in an active material solution for 15 minutes. The active material solution contains vanadyl sulfate, ammonium metatungstate and ammonium molybdate. The mass percentage of vanadyl sulfate is 6wt%, the mass percentage of ammonium metatungstate is 4wt%, and the mass percentage of ammonium molybdate is 10wt%.
[0033] 5) Activation: The module obtained in step 4) is dried and calcined to achieve high-temperature activation, with a drying temperature of 200° C. and a drying time of 6 h; and a calcination temperature of 400° C. and a calcination time of 3 h.
[0034] Testing of the regenerated denitrification catalyst revealed that its silicon removal rate reached 93%, arsenic removal rate was 97%, denitrification efficiency was 58.32%, and activity recovered to 99.8%.
[0035] Example 3 Compared with Example 1, the difference is: Pickling: The module was then immersed in a solution containing nitric acid, hydrochloric acid, and 0.1% BTA (pH controlled to be 4), and bubbling cleaned for 180 min at 40°C, with a cleaning liquid-to-solid ratio (solution volume / module mass) of 4 mL:1 g, a total weight concentration of nitric acid and hydrochloric acid of 0.1%, and a weight ratio of nitric acid to hydrochloric acid of 2:1. Others were the same as in Example 2.
[0036] Testing of the regenerated denitrification catalyst revealed that its silicon removal rate was 84%, arsenic removal rate was 91%, denitrification efficiency was 56.98%, and activity was restored to 96.6%.
[0037] Comparative Example 1 Compared with Example 2, the difference is that the chemical washing in Example 2 is removed, that is, after the acid washing in step 2), step 3) is directly performed.
[0038] The rest is the same as Example 2.
[0039] The regenerated denitrification catalyst was tested and found to have a silicon removal rate of 15.2%, an arsenic removal rate of 89.6%, a denitrification efficiency of 30.41%, and an activity recovery of 57.7%.
[0040] Comparative Example 2 Compared with Example 2, the difference is: Step 2) Chemical washing: Immerse the module in a solution containing 10% nitric acid and 0.5% corrosion inhibitor for bubbling cleaning for 120 minutes (at room temperature), and the cleaning liquid-to-solid ratio (solution volume / module mass) is 4 mL:1 g.
[0041] The rest is the same as Example 2.
[0042] The regenerated denitrification catalyst was tested and found to have a silicon removal rate of 15.7%, an arsenic removal rate of 89.3%, a denitrification efficiency of 31.02%, and an activity recovery of 56.8%.
[0043] Comparative Example 3 Compared with Example 2, the difference is that the order of acid washing and alkali washing in step 2) is changed, that is, acid washing is performed first and then alkali washing is performed.
[0044] The rest is the same as Example 2.
[0045] Testing of the regenerated denitrification catalyst revealed that its silicon removal rate was 80.2%, arsenic removal rate was 90.4%, denitrification efficiency was 29.3%, and activity was recovered to 38.5%.
[0046] Comparative Example 4 Compared with Example 2, the difference is: Pickling: The module was immersed in a solution containing nitric acid, hydrochloric acid and 0.3% MBT (pH was controlled at 4), and bubbled for cleaning at 60°C for 240 minutes. The cleaning liquid-to-solid ratio (solution volume / module mass) was 4 mL:1 g. The total weight concentration of nitric acid and hydrochloric acid was 0.1%, and the weight ratio of nitric acid to hydrochloric acid was 2:1.
[0047] The rest is the same as Example 2.
[0048] The regenerated denitrification catalyst was tested and found to have a silicon removal rate of 83.7%, an arsenic removal rate of 90.2%, a denitrification efficiency of 47.8%, and an activity recovery of 89.7%.
[0049] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0050] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A method for regenerating a silicon-arsenic poisoned denitration catalyst, characterized in that: The following steps are included: 1) Blow off the soot and clean the silicon-arsenic poisoned denitrification catalyst; 2) The cleaned silicon-arsenic poisoned denitrification catalyst is subjected to alkali washing, acid washing and chemical washing; The pickling solution is a mixture of acid and copper corrosion inhibitor; the chemical washing solution is a mixture of hydrofluoric acid and corrosion inhibitor; 3) Then clean it; 4) Supplement active substances; 5) Drying and calcining to obtain the regenerated denitration catalyst.
2. The regeneration method according to claim 1, characterized in that: The washing in step 1) is performed by bubbling in an aqueous solution at pH 7 to 9.
3. The regeneration method according to claim 1, characterized in that: The alkali washing solution in step 2) is a sodium hydroxide or potassium hydroxide aqueous solution with a mass concentration of 5-20%, and the alkali washing temperature is 80-100°C.
4. The regeneration method according to claim 1, characterized in that: In the pickling solution in step 2), the acid is sulfuric acid, nitric acid or hydrochloric acid, the copper corrosion inhibitor is BTA or TTA, the pH is controlled to be 3-5, the mass concentration of the copper corrosion inhibitor is 0.1-0.3%, and the pickling temperature is 40-60°C.
5. The regeneration method according to claim 1, characterized in that: In the chemical washing solution in step 2), the mass concentration of hydrofluoric acid is 3% to 10%, and the mass concentration of corrosion inhibitor is 0.2% to 0.5%.
6. The regeneration method according to claim 1, characterized in that: The cleaning in step 3) is performed by bubbling in an aqueous solution at a pH of 5 to 7.
7. The regeneration method according to claim 1, characterized in that: The active substances in step 4) are vanadyl sulfate, ammonium metatungstate and ammonium molybdate.
8. The regeneration method according to claim 7, characterized in that: In the active material, the mass concentration of vanadyl sulfate is 0.1% to 6%, the mass concentration of ammonium metatungstate is 0.5% to 4%, and the mass concentration of ammonium molybdate is 2% to 10%.
9. The regeneration method according to claim 1, characterized in that: The drying temperature in step 5) is 150° C. to 200° C., and the drying time is 6 to 12 hours.
10. The regeneration method according to claim 1, characterized in that: The calcination temperature in step 5) is 350° C. to 400° C., and the calcination time is 3 to 6 hours.